2005
DOI: 10.1128/mcb.25.10.4117-4128.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Small GTPase Rap1 and Extracellular Signal-Regulated Kinases by the Costimulatory Molecule CTLA-4

Abstract: The mitogen-activated protein kinase extracellular signal-regulated kinase (ERK) is activated following engagement of the T-cell receptor and is required for interleukin 2 (IL-2) production and T-cell proliferation. This activation is enhanced by stimulation of the coreceptor CD28 and inhibited by the coreceptor CTLA-4. We show that the small G protein Rap1 is regulated in the opposite manner; it is inhibited by CD28 and activated by CTLA-4. Together, CD3 and CTLA-4 activate Rap1 in a sustained manner. To deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 49 publications
(66 reference statements)
2
57
0
Order By: Relevance
“…Instead, our data provide evidence for a context-dependent regulation of T cell motility by CTLA-4, which is modulated by co-ligation of NKG2D. Integrin activation may be one component of this effect (21,62).…”
Section: Figurementioning
confidence: 61%
“…Instead, our data provide evidence for a context-dependent regulation of T cell motility by CTLA-4, which is modulated by co-ligation of NKG2D. Integrin activation may be one component of this effect (21,62).…”
Section: Figurementioning
confidence: 61%
“…on June 19, 2019. by guest www.bloodjournal.org From activation by TCR with Rap1GAP1 expression and enhanced TCR-mediated ERK activation. 116 These and related studies 67 have demonstrated a role for Rap1 to uncouple Ras-mediated ERK activation in peripheral T cells. 113 TCR function is enhanced by stimulation of the coreceptor CD28, which is characterized by enhanced ERK activation and IL-2 production 67,117 and the inhibition of Rap1 52,54 without effecting Ras.…”
Section: T Lymphocytes Rap1 Inhibition Of Erksmentioning
confidence: 91%
“…113 TCR function is enhanced by stimulation of the coreceptor CD28, which is characterized by enhanced ERK activation and IL-2 production 67,117 and the inhibition of Rap1 52,54 without effecting Ras. 113,116 It has been proposed that CD28 does this by inducing endogenous Rap1GAP activity. 67 In contrast to CD28, the coreceptor CTLA-4 (cytotoxic T lymphocyte associated protein-4) inhibits T-cell activation by limiting multiple signals downstream of TCR, including ERKs.…”
Section: T Lymphocytes Rap1 Inhibition Of Erksmentioning
confidence: 99%
“…kip1 that are implicated in T cell anergy and inhibition of cell cycle (49,50). In human filariasis, T cell unresponsiveness is associated with increased expression of E3 ubiquitin ligases (c-cbl, cbl-b, Itch, and Nedd4) that are often up-regulated in anergic T cells (10).…”
Section: Cd4mentioning
confidence: 99%